CCT251545 enhances drug delivery and potentiates chemotherapy in multidrug-resistant cancers by Rac1-mediated macropinocytosis. (January 2023) - Qin, Siyuan; Zhang, Zhe; Huang, Zhao; Luo, Yinheng; Weng, Ningna; Li, Bowen; Tang, Yongquan; Zhou, Li; Jiang, Jingwen; Lu, Yi; Shao, Jichun; Xie, Na; et al.
Abstract: It was well known that P-glycoprotein (P-gp/ABCB1) is a master regulator of multidrug resistance (MDR) in cancers. However, the clinical benefit from blocking this pathway remains inconclusive, which motivates a paradigm shift towards alternative strategies for enhancing drug influx. Using a patient-derived organoid (PDO)-based drug screening platform, we report that the combined use of chemotherapy and CCT251545 (CCT) displays robust synergistic effect against PDOs and reduces proliferation of MDR cancer cells in vitro, and results in regression of xenograft tumors, reductions in metastatic dissemination and recurrence rate in vivo . The synergistic activity mediated by CCT can be mainly attributed to the intense uptake of chemotherapeutic agents into the cells, accompanied by alterations in cell phenotypes defined as a mesenchymal epithelial transformation (MET). Mechanistically, analysis of the transcriptome coupled with validation in cellular and animal models demonstrate that the chemosensitizing effect of CCT is profoundly affected by Rac1-dependent macropinocytosis. Furthermore, CCT binds to NAMPT directly, resulting in elevated NAD levels within MDR cancer cells. This effect promotes the assembly of adherents junction (AJ) components with cytoskeleton, which is required for continuous induction of macropinocytosis and consequent drug internalization. Overall, our results illustrate the potential use of CCT as a combination partner for the commonly used chemotherapeutic drugs in the management of MDR cancers. Graphical Abstract: ga1